Social Media and It’s Implication in Health Care: A Literature Review - Hutapea, Dwight Mahaputera Marulitua; Hutapea, Kimberley Maharani Maulibung (Jurnal Keperawatan Priority, 2024)
Social media is a platform to be shared with the public and identify different effects on patients. For example, their autonomy by complementing the information provided by health care to provide psychosocial support, and improve service delivery. Social media have effects on both patients and the wider health care system. Therefore, it is important to identify its implications for the healthcare system. This paper reviews the literature and briefs about social media and its implications in health care. This literature review is synthesized based on empirical evidence derived from the research literature from 2017-2023 and consists of 14 relevant articles from various online databases such as ScienceDirect, PUBMED, CINAHL, and Allied Health Literature. Social media is spreading across healthcare it increases patient awareness and satisfaction, which helps in improving the effectiveness of communication and satisfaction. Social media is mainly for social support, emotional support, esteem support, and network support. The implication of social media use by patients was also to affect the healthcare and patient's relationships by stimulating equal communication between the patient and healthcare, shorter relationships, increased switching healthcare, harmonious relationship, and suboptimal interaction between the patient and healthcare.